A microfluidic model of human vascularized breast cancer metastasis to bone for the study of neutrophil-cancer cell interactions. (15th December 2022) - Crippa, Martina; Talò, Giuseppe; Lamouline, Anaïs; Bolis, Sara; Arrigoni, Chiara; Bersini, Simone; Moretti, Matteo
Abstract: The organ-specific metastatization of breast cancer to bone is driven by specific interactions between the host microenvironment and cancer cells (CCs). However, it is still unclear the role that circulating immune cells, including neutrophils, play during bone colonization (i.e. pro-tumoral vs. anti-tumoral). Here, we aimed at analyzing the migratory behavior of neutrophils when exposed to breast CCs colonizing the bone and their contribution to the growth of breast cancer micrometastases. Based on our previous bone metastasis models, we designed a microfluidic system that allows to independently introduce human vascularized breast cancer metastatic seeds within a bone-mimicking microenvironment containing osteo-differentiated mesenchymal stromal cells and endothelial cells (ECs). ECs self-assembled into microvascular networks and connected the bone-mimicking microenvironment with the metastatic seed. Compared to controls without CCs, metastatic seeds compromised the architecture of microvascular networks resulting in a lower number of junctions (5.7 ​± ​1.2 vs. 18.8 ​± ​4.5, p ​= ​0.025) and shorter network length (10.5 ​± ​1.0 vs. 13.4 ​± ​0.8 [mm], p ​= ​0.042). Further, vascular permeability was significantly higher with CCs (2.60 ​× ​10 −8 ​± ​3.59 ​× ​10 −8 ​vs. 0.53 ​× ​10 −8 ​± ​0.44 ​× ​10 −8 [cm/s], p ​= ​0.05). Following metastatic seed maturation, neutrophils were injected into microvascular networks resulting in a higher extravasation rate when CCs were present (27.9 ​± ​13.7 vs. 14.7 ​± ​12.4 [%], p ​= ​0.01). Strikingly, the percentage of dying CCs increased in presence of neutrophils, as confirmed by confocal imaging and flow cytometry on isolated cells from the metastatic seeds. The biofabricated metastatic niche represents a powerful tool to analyze the mechanisms of interaction between circulating immune cells and organ-specific micrometastases and to test novel drug combinations targeting the metastatic microenvironment. Graphical abstract: Image 1